STRES DI TEMPAT KERJA: PERBANDINGAN ANTARA GENDER DENGAN PEKERJAANNYA - KB, Dwi Hastjarja (Universitas Slamet Riyadi, 2004)
ABSTRACT Stress is used to show an unwanted condition, unpleasure one, both mentally (emotion) and physically. Stress not only shows an unpleasure condition (negative) but also a pleasure one (positive). One's performance is influenced negatively when he or she has a heavy loadwork. It is a potential condition in emerging stress. The emerged stress will give bad influence to someone, in his or her work and life quality. Career woman that faced to many works usually has more stress than man, thus it results in disturbing physic and mental healthy and can hinder the goal to reach top manager position. There are stress differences in workplace that can happen to any management level, and can happen both to man and woman. Thus we will see how far does that stress happen in workplace and influence one's performance, both man and woman. Â Keywords: stress at workplace, performance, stress influence, work and life quality